2001
DOI: 10.1007/s11916-001-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and management of cluster headache

Abstract: Cluster headache is an uncommon yet well-defined neurovascular syndrome occurring in both episodic and chronic varieties. The most striking feature of cluster headache is the unmistakable circadian and circannual periodicity. Inheritance may play a role in some families. The attacks are of extreme intensity, of short duration, occur unilaterally, and are accompanied by signs and symptoms of autonomic dysfunction. In contrast to migraine, during an attack the cluster patient prefers to pace about. Attacks frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 54 publications
0
46
0
5
Order By: Relevance
“…Results suggest that MEL treatment or PG prevent agerelated thymus involution through regulation of thymocyte apoptosis which, in turn, occurs through modulation of the pituitary-adrenal axis and zinc turnover determined by the pineal hormone 231 . Studies have found melatonin useful in cocaine abuse 232 , seasonal affective disorder 233,234 , delirium 235 , headache 236,237 , gallstone 238,239 , and amyotrophic lateral sclerosis 240 . Few studies have suggested melatonin as an effective radioprotective agent [241][242][243][244][245] .…”
Section: Miscellaneousmentioning
confidence: 99%
“…Results suggest that MEL treatment or PG prevent agerelated thymus involution through regulation of thymocyte apoptosis which, in turn, occurs through modulation of the pituitary-adrenal axis and zinc turnover determined by the pineal hormone 231 . Studies have found melatonin useful in cocaine abuse 232 , seasonal affective disorder 233,234 , delirium 235 , headache 236,237 , gallstone 238,239 , and amyotrophic lateral sclerosis 240 . Few studies have suggested melatonin as an effective radioprotective agent [241][242][243][244][245] .…”
Section: Miscellaneousmentioning
confidence: 99%
“…Headaches: Several clinical studies indicate that supplementation with melatonin is an effective preventive treatment for migraines and cluster headaches 26,27 . , and is being considered for bipolar and other disorders where circadian disturbances are involved 28 .…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
“…The pain intensifies rapidly, peaking in 5-10 min and may stay at maximal intensity for 45-90 min. After the attack the patient is pain-free but exhausted [3].…”
Section: Clinical Manifestationsmentioning
confidence: 99%